PERKEMBANGAN DESA WISATA JATILUWIH SETELAH UNESCO MENETAPKAN SUBAKNYA SEBAGAI BAGIAN DARI WARISAN BUDAYA DUNIA - Dewa Ayu Diyah Sri Widari (Magister Tourism Study, Faculty of Tourism, Udayana University, 2015)
This article identifies the social, cultural, and economicdevelopment of Jatiluwih tourism village after subak (rice fieldand its irrigation cultural system) in this village was decreed byUNESCO as a World’s Cultural Heritage in 2012, under the labelCultural Landscape of Bali Province: the Subak System as aManifestation of the Tri Hita Karana. It also discusses tourists’perception to the rice field tourist attraction. The data werecollected through observation, interview, and documentary study,and then descriptively and qualitatively analyzed. The informantswere selected using the purposive sampling technique and theaccidental sampling technique. The study shows that the mutualcooperation, the rituals related to the farming activities, and riceplanting system were still well maintained by farmers of the subakmember. The traditional arts were conserved and developed, andthe social organization were also well maintened. The economicaspects which includes job and business opportunities, incomeand investment have improved. The local people’s participationin the planning and controlling phases were manipulative andfunctional. In the development phase, the local people participatedactively. While tourist’s perception on subak is good, but that is notthe case on the poor condition of public facilities and informationservice by local management.